Carbon–Oxygen Homocoupling of 2-Naphthols through Electrochemical Oxidative Dearomatization - Chen, Ting; Chen, Song; Fu, Shaomin; Qin, Song; Liu, Bo (Synlett, 2019)
A homocoupling reaction of 2-naphthols with formation of a C–O bond through electrochemical oxidative dearomatization in the presence of catalytic amounts of ferrocene and a ruthenium complex was developed. Mechanistic studies revealed that the reaction might proceed through coupling between two identical radical species. Moreover, a gram-scale experiment was performed to illustrate the potential practicability of this methodology in organic synthesis.
Keywords: electrochemistry; homocoupling; C–O bond formation; naphthols; dearomatization; naphthyloxynaphthalenones